Income Mobility Breeds Tolerance for Income Inequality: Cross-National and Experimental Evidence. (May 2016) - Shariff, Azim F.; Wiwad, Dylan; Aknin, Lara B.
American politicians often justify income inequality by referencing the opportunities people have to move between economic stations. Though past research has shown associations between income mobility and resistance to wealth redistribution policies, no experimental work has tested whether perceptions of mobility influence tolerance for inequality. In this article, we present a cross-national comparison showing that income mobility is associated with tolerance for inequality and experimental work demonstrating that perceptions of higher mobility directly affect attitudes toward inequality. We find support for both the prospect of upward mobility and the view that peoples' economic station is the product of their own efforts, as mediating mechanisms.